Enzymes as Enhancers for the Biodegradation of Synthetic Polymers in Wastewater. (16th January 2018) - Haernvall, Karolina; Zitzenbacher, Sabine; Biundo, Antonino; Yamamoto, Motonori; Schick, Michael Bernhard; Ribitsch, Doris; Guebitz, Georg M.
Abstract: Synthetic polyesters are today the second‐largest class of ingredients in household products and are entering wastewater treatment plants (WWTPs) after product utilization. One approach to improve polymer biodegradation in wastewater would be to complement current processes with polyester‐hydrolyzing enzymes and their microbial producers. In this study, the hydrolysis of poly(oxyethylene terephthalate) polymer by hydrolases from wastewater microorganisms was investigated in vitro and under realistic WWTP conditions. An esterase and a cutinase from Pseudomonas pseudoalcaligenes and a lipase from Pseudomonas pelagia were heterologously expressed in Escherichia coli BL21‐Gold(DE3) and were purified by a C‐terminal His6 tag. The hydrolases were proven to hydrolyze the polymer effectively, which is a prerequisite for further biodegradation. The hydrolases maintained high activity up to 50 % upon lowering the temperature from 28 to 15 °C to mimic WWTP conditions. The hydrolases were also not inhibited by the wastewater matrix. Polyester‐hydrolyzing enzymes active under WWTP conditions and their microbial producers thus have the potential to improve biological treatment of wastewater rich in synthetic polymers. Abstract : Waste not, want not : Enzymatic hydrolysis of a commonly used polymer in household products is investigated in vitro and under realistic wastewater‐treatment conditions by using three hydrolases from typical wastewater microorganisms. Enzymes indeed have great potential and are likely to play an important role in improving the biological treatment of wastewater rich in synthetic polymers.